Enhanced ferroelectric and piezoelectric performance of (Ba0.85Ca0.15)(Zr0.1Ti0.9)O3 lead-free ceramics upon Ce and Sb co-doping. Issue 5 (12th January 2021) - Zheng, Weijie; Lin, Jiaqi; Liu, Xinmei; Yang, Wenlong; Li, Yuanshuo
Abstract : (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9− x Ce x )O3 + y Sb ceramics prepared by the conventional solid-state reaction. Abstract : (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9− x Ce x )O3 + y Sb (abbreviated as BCZTC x S y ) ceramics were prepared by the conventional solid-state reaction. The effect of the co-doping of Ce and Sb on the phase structure, microstructure, dielectric, and ferroelectric and piezoelectric performances of BCZTC x S y ceramics were investigated systematically. The results indicated that the obtained ceramics are composed of coexisting rhombohedral and tetragonal phases. Significant improvements were also observed in the growth of grain, relative density, as well as electrical performance. After co-doping 0.05 mol% Ce and 0.10 mol% Sb, the sizes of crystalline grains reached the maximum. The following optimal properties were obtained: ε r = 2353, tan  δ = 0.026, T c = 109.4 °C, P max = 17.65 μC cm −2, P r = 10.43 μC cm −2, E c = 2.88 kV cm −1, S max = 0.125%, = 417 pm V −1, d 33 = 372 pC N −1 . With the increase in dopants, the diffuseness γ increased from 1.663 to 1.733, indicating a more relaxed ferroelectric characteristic. All improvements show that BCZT ceramics co-doped with Ce and Sb could be promising candidates in lead-free devices.